Obtaining and characterizing açaí seed (Euterper Oleracea) and bacaba peel (Oenocarpus Bacaba) flors (Research, Society and Development, 2021)
Those from the Amazon and Cerrado biomes, such açaí (Euterper fruit oleracea) and bacaba (Oenocarpus bacaba), are appreciated for their exotic flavors, nutritional and functional potential. The search for healthy foods and the discovery of functional nutrients existing in fruit residues, has increased the relevance of by-products derived from peels and seeds or seeds, leading to the growth of the food industry. Therefore, the objective of the study was to produce flour from the açaí core and the peel bacaba, as well its physical, chemical and technological characterization. The açaí seed was purchased in the city of Imperatriz (MA) and the bacaba was obtained in the village of Pedra Branca Terra Indígena Krahô in the state of Tocantins. The residues were dried in an oven with air circulation, at a temperature of 50ºC. Flours from açaí stone and bacaba peel presented considerable values of nutrients, being a good source of proteins, lipids and carbohydrates, besides presenting low humidity and acidic pH contributing as a barrier against the growth of microorganisms. The gray values obtained in both flours are in accordance with Brazilian legislation. The flour from the açaí core and the bacaba peel showed low luminosity and the chroma (C *) and hue angle (h *) values indicated a reddish color for all flours. The results of technological analysis, such as absorption and solubility index, show potential for the elaboration of new foods.